Toxicity and molecular docking approach phenolic extract of Crescentia cujete L against the enzymes glutathione peroxidase and cathepsin K - Lia Nurliana; Meri Yulvianti; Ahmad Hariri; Suaedah Suaedah; Herayati Herayati; Agus Rochmat; Yeyen Maryani (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
Osteoporosis is a metabolic bone disease characterized by a decrease in bone mass, caused by a reduction in bone matrix and minerals accompanied by microarchitectural deterioration of bone tissue. Factors such as hormone production, the aging process, and the formation of free radicals due to oxidative stress by Reactive Oxygen Species (ROS) can stimulate bone resorption. The content of secondary metabolite compounds in Crescentia cujete L. has medicinal properties for diseases. Purpose: this study was to determine the phenolic compound of Crescentia cujete L which has acted as an anti-osteoporosis with the approach of docking in silico. Extraction and partitioning of Crescentia cujete L fruit extracts in this study used n-hexane and toluene solvents with the aim of obtaining phenolic group compounds, knowing the toxicity value of partition results, obtaining the structure of phenolic compounds that have the potential to be anti-osteoporosis, and validating the ability of these phenolic compounds as anti-oxidants. As a result, n-hexane and toluene extracts are known to contain elevated levels of active and toxic compounds with LC50 values of 31.79 ppm and 93.49 ppm, respectively. The phytochemical test shows the presence of phenolic groups with maximum wavelengths at 302-320 nm. Benzene acetate, trans-cinnamic acid, and propanoic acid have the lowest affinity bonds with receptor 2F8A (Glutathione peroxidase); -4.21, -4.81, and -4.72 kcal/mol. Whereas at the 3KWZ receptor (Cathepsin K); -6.0, -5.4, and -5.0 kcal/mol. Conclusion: The phenolic compound of Crescentia cujete extract L can be used as an alternative treatment for osteoporosis by inhibiting the enzymes Glutathione peroxidase and Cathepsin K